Application of the Theory of Planned Behaviour on impulse buying behaviour in an internationalized shopping centre. - Toh, Evelyn Bee Hwa *; Selvan, Perumal (2015)
The study focuses on an Internationalized Shopping Centre in located in Malaysia. It is internationalized because it was originally owned and operated by a Malaysian conglomerate (Sunway Group) but was subsequently taken over by a Singaporean based group. The interesting phenomenon about this transformed shopping centre is the business of mergers and acquisitions by localized Singaporean MNCs. Hence, the study examines the effect of perceived crowding and the appearance of service employees at a shopping centre on impulse buying behaviour. This study is guided by the Theory of Planned Behaviour (TPB) model as well as impulse buying literature, seeking to investigate how the three constructs (attitude, subjective norm and perceived behavioural control) would influence shoppers’ impulse buying intention which would lead to impulse buying behaviour. Data to be collected from a shopping centre (Sunway Pyramid) located in the Klang Valley, using the mall intercept method, will only be conducted on weekends when the shopping centre is usually crowded.